The life and thought of Charles Chauncy (1705-1787) - Gibbs, Norman B.; Gibbs, Lee W. (Lewiston : Edwin Mellen Press, 2011)
A spiritual biography of Charles Chauncy which, for the first time, provides an alternative and balanced view of his theology and life.
Chapter 15: Kenosis in the New TestamentChapter 16: The Kenosis in the Writings of Chauncy; Chapter 17: Closure to Part 3; Selected Bibliography; Primary Sources Cited by Chauncy; Index
Includes bibliographical references and index.
Description based upon print version of record.
Keywords: Chauncy, Charles, 1705-1787.; Congregational churches -- Clergy -- Biography; Massachusetts -- Church history -- 18th century; Theology, Doctrinal -- Massachusetts -- History -- 18th century; Religion; RELIGION / Christianity / Presbyterian; Chauncy, Charles, -- 1705-1787.; Congregational churches -- Clergy -- Biography; Theology, Doctrinal -- Massachusetts -- History -- 18th century; Massachusetts -- Church history -- 18th century; Electronic books